The role of hippocampal calcium-permeable AMPA receptors in network activity and behaviour - Cooper, M (2018)
Parvalbumin-expressing (PV+) interneurons within the hippocampus play important roles in controlling spike timing and spike rates in circuits within the hippocampus, a brain region widely associated with various aspects of memory and spatial navigation. Due to minimal expression of the GluR2 AMPA receptor subunit, excitatory synapses onto PV+ interneurons are dominated by inwardly rectifying, Ca2+-permeable AMPA receptors (CP-AMPARs); in contrast, many other cell types, including principal cells, predominantly express GluR2-containing receptors. In addition to contributing to rapid excitation of these fast-spiking cells, CP-AMPARs are capable of mediating synaptic plasticity independent of NMDA receptors, with LTP following anti-Hebbian rules. Given the central role of PV+ interneurons in multiple aspects of hippocampal network function, including theta- and gamma-frequency oscillatory patterns of activity, the work in this thesis explored what impact manipulating neuronal recruitment and synaptic plasticity mediated by these receptors would have on the function of the hippocampal network and associated behaviour. Initial experiments focused on application of different antagonists with varying selectivity for GluR2-lacking CP-AMPARs over other AMPARs to in vitro slice preparations, which reduced the power of carbachol-evoked gamma oscillations whilst variably affecting oscillation frequency. In vivo infusion of one such antagonist, NASPM, into dorsal hippocampus resulted in a dose-dependent impairment in spatial working memory in mice, further supporting the widely-reported link between PV+ interneuron activity, hippocampal network function, and short-term spatial memory. Subsequent experiments aimed to more selectively manipulate Ca2+ flow through CP-AMPARs whilst conserving overall excitability (charge transfer), via transfection of PV+ interneurons with a virus driving Cre-dependent artificial expression of the Q/R-edited GluR2 subunit. Selective transfection of hippocampal PV+ interneurons in PV-Cre mice altered various single-cell and network properties in vitro, including reductions in synaptically-evoked dendritic calcium signals, resistance to the effects of NASPM on hippocampal gamma oscillations, and impairments in induction of anti-Hebbian plasticity. After determining viral expression and functionally validating the AMPAR manipulation in vitro, a behavioural characterisation of the effects of removing Ca2+ permeability from hippocampal PV+ interneurons was performed, with a cohort of mice given bilateral, complete (dorsal and ventral) hippocampal injections of the floxed GluR2 virus or a control Cre-dependent GFP virus. The GluR2-transfected animals exhibited impairment in spatial reference memory acquisition. However, the GluR2-transfected animals exhibited a substantial, delay-dependent impairment on the spatial working memory, rewarded alternation T-maze task compared to controls. They also exhibited worsening performance with accumulating trials across a session, independent of delay. Additionally, the GluR2-transfected animals took longer to learn new locations of an escape platform in a serial reversal water maze task. The results from the behavioural characterisation suggest that substitution of CP-AMPARs in hippocampal PV+ interneurons with GluR2-containing AMPARs leads to memory impairments due to interference between competing memory traces, potentially as a consequence of impaired AMPAR-mediated plasticity.